Treatment of patients with Waldenström macroglobulinaemia: clinical practice guidelines from the Myeloma Foundation of Australia Medical and Scientific Advisory Group. Issue 1 (January 2017) - Talaulikar, Dipti; Tam, Constantine S.; Joshua, Douglas; Ho, Joy Phoebe; Szer, Jeff; Quach, Hang; Spencer, Andrew; Harrison, Simon; Mollee, Peter; Roberts, Andrew W.; Horvath, Noemi; Lee, Cindy; et al.
Abstract : Waldenström macroglobulinaemia (WM) is an indolent B‐cell malignancy characterised by the presence of immunoglobulin M (IgM) paraprotein and bone marrow infiltration by clonal small B lymphocytes, plasmacytoid lymphocytes and plasma cells. The symptoms of WM are protean, often follow an asymptomatic phase and may include complications related to the paraneoplastic effects of IgM paraprotein. The revised 2016 World Health Organization classification includes the MYD88 L265P mutation, which is seen in >90% of cases, within the diagnostic criteria for WM. While treatment of WM has often been considered together with other indolent B cell lymphomas, there are unique aspects of WM management that require specific care. These include the unreliability of IgM and paraprotein measurements in monitoring patients prior to and after treatment, the lack of correlation between disease burden and symptoms and rituximab‐induced IgM flare. Moreover, while bendamustine and rituximab has recently been approved for reimbursed frontline use in WM in Australia, other regimens, including ibrutinib‐ and bortezomib‐based treatments, are not funded, requiring tailoring of treatment to the regional regulatory environment. The Medical and Scientific Advisory Group of the Myeloma Foundation Australia has therefore developed clinical practice guidelines with specific recommendations for the work‐up and therapy of WM to assist Australian clinicians in the management of this disease.